EKSPLORASI PERSPEKTIF BARU : KONTRIBUSI AKUNTANSI MANAJEMEN LINGKUNGAN DALAM KINERJA BISNIS DAN PEMBANGUNAN BERKELANJUTAN - Andrianto, Andrianto (Majalah Ekonomi, 2026)
This study aims to analyze the contribution of Environmental Management Accounting (EMA) to business performance and sustainable development in the Indonesian manufacturing sector. The research method used qualitative approaches. Qualitative data were obtained through in-depth interviews with managers and accountants in the cement, steel, and paper industries. The research findings indicate that EMA has a positive effect on business performance. Sustainable development is proven to mediate the relationship between EMA and business performance.Results also found significant differences between sectors, with the cement and steel industries being more progressive than the paper industry.The novelty of this research lies in the evidence that EMA in Indonesia is more dominant in increasing sustainable development than short-term profitability, with external factors such as regulations and the global market playing a stronger role than internal factors. This research also emphasizes the urgency of strengthening regulations and human resource capacity as prerequisites for accelerating EMA adoption.